Políticas culturais e economia da cultura no sertão paraibano: o caso vale dos dinossauros - Silva, Eduardo Pordeus (2009)
The culture and cultural politics have become considerable topics from the economic point of view, and mainly, from the social development. In this context, the cultural patrimony, particularly, no matter its denomination (historical, artistic, archaeological and paleontological patrimony) or its way of expression (material or non material), deserves the attention from the public politics in a way to excite the local economy, in view of the innovating aspects of the specified way of cultural expression. It comes from the principle in which the acts of the State should focus on the valorization of the human being, excepting the needing of collecting financial resources. This way, the state citizen acts for the improvement or solidification of the public politic which respects and promotes the cultural diversity and the rights to culture. For this reason, we mention topics that need scientific investigation so that to deepen the discussion about the fulfillment of the present Brazilian Constitution, and all the other legal rules that aim the social justice through the rise of culture. In this discussion, it is essential to instigate the new way of economy, especially about the conduct of the cultural patrimony, the reason why the current search, specifically, points out the ideas and actions of the paleontological patrimony Valley of Dinosaurs (Vale dos Dinossauros), located in Sousa, Paraiba, Brazil. It has been verified the integrated ways of the public politics (in particular, those that allow favouring the enjoyment and the sustainable usufruct of this cultural patrimony. Besides, according to studies of this case, it was possible to verify, since a long time ago, the non execution or the disrespect to the laws that foresee the protection of the material patrimony of the search, because of the absence of projects, programs of effective actions for the conservation and valorization of the cultural property, and this, difficultates plans for the tourism and envolvement of the local community and its management, consequently, the aims of human development and cultural citizenship are delayed.